DEVELOPMENT OF INTEGRATED SCIENCE-BASED SCIENCE LITERACY SKILLS INSTRUMENTS USING THE RASCH MODEL - Susongko, Purwo; Widiatmo, H; Kusuma, M; Afiani, Y (Unnes Science Education Journal, 2019)
The objectives of this study are: (1) To compile a test construction to measure scientific literacy skills of integrated science-based high school MIPA program students by referring to the achievements of scientific literacy according to the 2015 PISA standard, (2) Conduct validation of test items using Rasch modeling. The research design uses ADDIE procedural models (Analysis, Design, Development, Implementation, Evaluation). There are three types of validation in the development of instruments namely content validation, psychometric aspects validation and extract validation with Rasch modeling. The instruments were tested on class XII students of the MIPA Program from Tegal City 2 High School and Tegal City 3 High School involving 112 students. The construction of the test consisted of 17 integrated science cases presented in the form of tests each consisting of three questions referring to scientific literacy competencies according to PISA standard 2015. Test items have fulfilled the validity of the content aspects and psychometric aspects. Extract validation using Rasch modeling gives the following results: (1) The level of item difficulty is in the range of -3 to 3, (2) There are 16 items that are compatible with modeling, (3) There are 97.32% of student responses suitable with modeling, (4) There are 2 items containing DIF. Based on consideration of all aspects of validity, there are 14 items worthy of being used as items for scientific literacy tests.